Estudo de revestimento compósito de porcelanato e borracha reciclada para atenuação do ruído de impacto - Klippel Filho, Sérgio (Universidade do Vale do Rio dos Sinos, 2025)
When analyzing building acoustics, the propagation of impact sounds through the structure of the building can be considered one of the most relevant problems, being a recurring subject of complaints. In these cases, floating floor systems are efficient solutions to reduce the transmission of vibrations generated by impacts on floors, consisting of a rigid walking surface on a resilient material. Acting as a spring, the resilient layer must have damping properties and compression strength against permanent and accidental loads adequate to guarantee its performance over time. In this context, the objective of this study is to develop and evaluate lightweight floating floors formed by ceramic tiles and recycled rubber agglomerate mats to attenuate the transmission of impact sounds in vertically adjacent rooms, analyzing their current and future performance. The study was based on the development of a lightweight floating floor and the physical and acoustic characterization of its components, proposing a model to predict the reduction of impact sounds, calibrated from full-scale measurements in a laboratory environment (ISO 10140), based on the dynamic stiffness (ISO 9052-1) of the rubber agglomerate mats and the physical characteristics of the rigid walking layer. The determination of the future behavior of the lightweight floating floor was carried out based on the compression creep test (ISO 16534) and the evaluation was carried out from its virtual application in a hypothetical building, considering direct and indirect transmission (ISO 12354-2). The results indicated that the lightweight floating floor compositions have adequate performance, with ΔLw values in the order of 16 to 18 dB, demonstrating efficiency, considering that the compositions have a total thickness of 11.5 to 20.5 mm. In the time domain, when subjected to loads of up to 15 years, the damping capacity, in terms of weighted impact sound pressure levels reduction, of the compositions was reduced by up to 2 dB. However, the developed compositions have a considerable impact sounds reduction and adequate maintenance of performance in the time domain.
Keywords: Desempenho acústico; Isolamento aos sons de impacto; Materiais resilientes; Revestimento compósito de piso; Acoustic performance; Impact sound insulation; Resilient materials; Composite flooring; ACCNPQ::Engenharias::Engenharia Civil